MORPHOTECTONIC AND MORPHOMETRY CIMANDIRI ACTIVE FAULT FROM INSAR DIGITAL ELEVATION MODEL IN SUKABUMI DISTRICT, WEST JAVA - INDRAJATI (NIM: 22014012), RAHMAT
Cimandiri Fault can be traced from satelite image, lineation of hill and valley which start from Pelabuhan Ratu in Sukabumi District to Padalarang, Bandung District. This lineation length up to 200 km. Cimandiri Fault is active based on horizontal displacement around the fault from Global Positioning System measurement and shallow earthquake around fault. Because of rarely earthquake make the rupture and morphology from earthquake in this fault is hard to identified. Channel stepness index method, active fault mapping from 5 meter resolution digital elevation model and resistivity data can be use to identified fault trace. Fault scrap, stream terrace, river offset, and triangular facet which is the earthquake morphology can be identified from active fault mapping. The result from channel stepness index indicated there is active fault in the area with ksn > 60 m0.9). From resistivity interpretation, there are fault that cut surface sedimen to 25 meter depth,. Four fault segment have been identified from data integration, which is: Mekarasih, Cibuntu, Tanjungsari, and Gandasoli. Maximum moment magnitude from all segment is 7.05 Mw. Elastic dislocation model is used to simulate deformation around fault segment. The model show that uplift is on the southern part of fault and subsidence is on the north of the fault. Kinematic result from model show that the fault is oblique with thrust and sinistral movement.